Kabeljau-Discards in der Deutschen Bucht - Weber, Wolfgang (1996)
The German trawlfishery on cod in the German Bight causes discards. Their amount since 1983 has been estimated. The losses of millions of fish finally is the reason for losses of thousands of tonnes of valuable landings. The fishermen therefore should improve the selection rate of their nets.